Anestesia raquídea con dosis mínimas efectivas de bupivacaina hiperbárica al 0,5% más opioide versus anestesia raquídea con dosis habituales a pacientes sometidos a artroscopias del hospital Manuel Ygnacio Monteros de la ciudad de Loja, periodo abril 2013-enero 2014. - Sarmiento Álvarez, Karla Alexandra (2014)
Spinal anesthesia is a practice considered a safe technique, relatively easy to perform, that has prompted numerous researches with different drugs, different doses, looking to determine which drug or dose may provide satisfactory surgical anesthesia and postoperative analgesia for the patient. Objective: assess the quality of anesthesia and analgesia using the minimum effective dose of hyperbaric bupivacaine 0.5% with fentanyl vs usual dose of hyperbaric bupivacaine 0.5% with fentanyl in spinal anesthesia, in patients scheduled for arthroscopic surgery from the hospital Manuel Ignacio Monteros. Methods: this is a Clinical, prospective single-blind study. 60 patients ASA I and II distributed in two randomized study groups, in which two different doses for spinal anesthesia were applied for arthroscopy. The control group received 10 mg hyperbaric bupivacaine 0.5%, the low-dose group were administered 5 mg hyperbaric bupivacaine 0.5%, both with fentanyl 25 ug. after the first 5 minutes of completed the administration of the local anesthetic, was measured and recorded the level of sensory-motor block until its demise as well as the Monitoring of hemodynamic variables Results: with a low doses of hyperbaric bupivacaine 0.5% decreased, 26% bradycardias, 23% systolic hypotension, 17% (CI RAR: 0.98% - 32.36%) less diastolic hypotension. Regarding the duration of motor block, in the low dose group, the average time is 65 minutes, in the other group the average duration was 183 minutes the higher metameric level blocked in the control group reached T8 and in the low dose group reached T10, the duration of sensory block in the low dose group has on average 121 minutes, in the group of control has an average of 192.17 minutes. According to the visual analog scale (VAS) all patients were painless during surgery and postoperative, 67% who used a low dose, had a shorter stay time into the postoperative care room (95 minutes or less). Discussion and Conclusions: The use of low doses of hyperbaric bupivacaine 0.5% with addition of opioids is a good alternative to obtain a satisfactory surgical analgesia with rapid motor recovery, good metameric level and good hemodynamic stability.